Judicial Independence in Pakistan - ZULFIQAR, Rida (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
Independent judiciary is the justification of a balanced and disinterested and judiciously equitable civilization. Independence suggests that professionals in law can unobstructed deliver legal judgments whether involving powerful diplomats, executive characters, or average residents. Therefore, guaranteeing resolutions are built on vitality slightly than is the outcome of governmental tensions or is promoting some bulk. Founded with freedom, the judiciary system works as a defense of public equities and independence. In Pakistan, however, the Constitution designates an individualistic and non-interrupted judiciary but political authorities, from multiple years, have been doubled upon guaranteeing that the lawmakers or law implementers/ judges constantly survive in an environment of anxiety and address partial and advantageous determinations under the leadership and intentional power of the outside officials. This paper settles that an unconventional or independent judicial system may not denote the clarification to all the dilemmas of Pakistan but is the numerous significant paces towards resolving the obstacles covered by the country machinations. These hurdles have great impact on country’s overall judicial performance which turns it not a democratic state and throw critical observation over dependent proclaims of judicial system, where jury could not perform and execute rule of law individually. Furthermore, the historical events from 1947 to 1956 stand the revolution in constitutional corner of the state but unfortunately severe contamination in legislative system and interpretation of external bodies in organizational independency of law, upgraded nepotism and corruptions like threats in current infrastructure of administration.